Pneumatic Retinopexy in Rhegmatogenous Retinal Detachment : Case Series - Fauzan Teuku Banta; Ari Djatikusumo; Elvioza Elvioza; Gitalisa Andayani; Anggun Rama Yudhanta; Mario Marbungaran Hutapea; Andi Arus Victor (Majalah Oftalmologi Indonesia, 2019)
In the case of rhegmatogenous retinal detachment (RRD), pneumatic retinopexy is an alternative choice besides scleral buckling and pars plana vitrectomy. This case series describes two cases of RRD with superotemporal tear treated succesfully with pneumatic retinopexy. The expandable gas used in this study was 0.4 cc perfluoropropane (C3F8) gas, patient’s head is immediately positioned face down (prone), then slowly turned into an upright position in accordance with the tear for 1-3 days. Laser retinopexy using an argon laser is performed after the retina is properly reattached. Ten months after pneumatic retinopexy, the VA of RE in case I remained at 6/18 with reattached retina. At four weeks, VA of RE in case II was at 3/60 with reattached retina. VA of both cases was relatively satisfactory with retinal reattachment in a single procedure. The anatomical and functional success of pneumatic retinopexy is related to macular status before surgery, retinal detachment area, phakic status, or the presence of PVR and high myopia.